Somatotypes of elite male and female junior sambo athlete - Drid, P.; Tabakov, S.; Eliseev, S.; Selimovic, N.; Jaksic, D.; Trivic, T.; Ostojic, S. M. (Archives of Budo, 2018)
Background and Study Aim: Sambo is a relatively novel international martial art founded back in 1930`s. It is mainly characterized by specific throws, holds, arm and leg locks, where successful performance depend on specific technique and tactical skills along with optimal physical fitness. The aim of the present study was somatotype and anthropometric profiles of elite junior sambo athletes divided by weight categories.